AWDARMA TEORIYASÍNÍŃ RAWAJLANÍW BASQÍShLARÍ HÁM LINGVISTIKALÍQ ÁDIS - Erimbetova, Sh.A. (ILIM hám JÁMIYET, 2025)
This article provides information on the historical stages of translation theory and the theoretical foundations of its development. The tasks of linguistic, cultural, and communicative relations, which are widely used in the activities of translation theory, are also described. It is emphasized that linguocultural features, cultural interpretation, cultural vision, and creative abilities are the most important abilities that should be present in the translator’s activity.